Els llindars de les Alonsíades. Els paratexts en La Alonsíada, de Joan Ramis, i L'Alonsíada, de Vicenç Albertí. - MARTÍNEZ MAYOR, CARLOS (Scripta, 2017)
In 1818, the Menorcan enlightened Joan Ramis i Ramis (1746-1819) published La Alonsíada, an epic poem in Spanish that narrates the conquest by Alfons III of Aragon of the island of Menorca in 1287, then in Saracen hands. In the same year, the Catalan translation of the text, L'Alonsíada, was also printed by his contemporary Vicenç Albertí i Vidal (1786-1859). Although they are an original work and its translation, there are notable differences in the presentation of the two versions. These divergences affect aspects of civil and political nature, such as the purpose of each text or the audience to which they were addressed. In this line, the implications that arise from the paratexts present in each of the compositions are very interesting, since they show the different directions taken by each author. Thus, in this article, based on the paratextual typology proposed by Gérard Genette in Paratext: Tresholds of interpretation (1987), we have analyzed the differences between the paratexts of the two works. This study has allowed us to specify the civil and political points in which they diverge, the reasons that could cause the dissensions and the manner in which they are specified in the globality of the two works.